Hypocretin (Orexin) Replacement Therapies - Erica Seigneur; Luis de Lecea (Elsevier, 2020)
Twenty-two years after their discovery, the hypocretins (Hcrts), also known as orexins, are two of the most studied peptidergic systems, involved in myriad physiological systems that range from sleep, arousal, motivation, homeostatic regulation, fear, anxiety and learning. A causal relationship between activity of Hcrt and arousal stability was established shortly after their discovery and have led to the development of a new class of drugs to treat insomnia. In this review we discuss the many faces of the Hcrt system and examine recent findings that implicate decreased Hcrt function in the pathogenesis of a number of neuropsychiatric conditions. We also discuss future therapeutic strategies to replace or enhance Hcrt function as a treatment option for these neuropsychiatric conditions.